Enhancing Efl Students’ Interest and Learning Outcomes Through The Scientific Learning Approach - Sri Ningsih Rambe; Benni Ichsanda Rahman (LP. Ma'arif Janggan Magetan, 2023)
This study aims to investigate the effectiveness of the scientific learning approach to students' interest and learning outcomes in learning English in class IX MTs in Medan. Researchers used a descriptive quantitative approach and pre-test and post-test methods to collect data. The research population was 30 students. The sample used a saturated sample of 30 students (Sugiyono, 2017). For data collection, the researcher used 8 measurement indicators to measure students' learning interest and used the KKM standard = 75 to measure student learning outcomes through the test during the English learning activities. The data is then coded and tabulated using a percentage-based value. The results of these findings indicate that 1). According to the results of the standard pre-test, it was not possible to boost student learning interest and student learning outcomes in class. 2). The post-test using a scientific learning approach was said to be capable of increasing student learning interest and student learning outcomes in class when studying English.